The objective of the study are to analyze the level of technical efficiency of the production of red chili,(b) to analyze factors that influence the production of red chili, (c) to analyze the social-economic factors that affect inefficiency technically of red chili, and (d) to analyze the behavior of red chili farmers in facing price risk. The stochastic production frontier is used to estimate the production function. Results showed that most variables, both technical and socio-economic factor - Saptana .; Arief Daryanto; Heny K. Daryanto; Kuntjoro . (Forum Pasca Sarjana, 2011)
The objective of the study are to analyze the level of technical efficiency of the production of red chili,(b) to analyze factors that influence the production of red chili, (c) to analyze the social-economic factors that affect inefficiency technically of red chili, and (d) to analyze the behavior of red chili farmers in facing price risk. The stochastic production frontier is used to estimate the production function. Results showed that most variables, both technical and socio-economic factors, have signs as expected and most significant. The average level of technical efficiency (TE) for both big red chili and curly red chili are 0.83 and 0.86, respectively. Several socio-economic factors that significantly affect technical inefficiency includes total income, ratio income of red chili on the total household income, ratio of red chili farming plots to the total cultivated land, and variable experience of peasant households in red chili. The behavior of big red chili farmers in facing the price risk is risk averse, meanwhile curly the red chili farmers’ is a risk taker. Important policy implication is to increase technical skills and managerial capabilities at less than 0.80 technical efficiency group. Future technological development can be done by good agriculture pratices and standar operating procedure on red chili farming, that is hybrid seed use, balance and complete fertilizer use, manure use and integrated pest management practices. Key words: technical efficiency, risk, stochastic production frontier, red chilies